Heart Rate Recovery in Asymptomatic Patients with Chagas Disease - Alencar, Maria Clara Noman de; Rocha, Manoel Otávio da Costa; Lima, Márcia Maria de Oliveira; Costa, Henrique Silveira; Sousa, Giovane Rodrigo; Carneiro, Renata de Carvalho Bicalho; Silva, Guilherme Canabrava Rodrigues; Brandão, Fernando Vieira; Kreuser, Lucas Jordan; Ribeiro, Antonio Luiz Pinho; Nunes, Maria Carmo Pereira (PloS one, 2014)
Chagas disease patients with right bundle-branch block (RBBB) have diverse clinical presentation and prognosis, depending on left ventricular (LV) function. Autonomic disorder can be an early marker of heart involvement. The heart rate recovery (HRR) after exercise may identify autonomic dysfunction, with impact on therapeutic strategies. This study was designed to assess the HRR after symptom-limited exercise testing in asymptomatic Chagas disease patients with RBBB without ventricular dysfunction compared to patients with indeterminate form of Chagas disease and healthy controls. One hundred and forty-nine subjects divided into 3 groups were included. A control group was comprised of healthy individuals; group 1 included patients in the indeterminate form of Chagas disease; and group 2 included patients with complete RBBB with or without left anterior hemiblock, and normal ventricular systolic function. A symptom-limited exercise test was performed and heart rate (HR) response to exercise was assessed. HRR was defined as the difference between HR at peak exercise and 1 min following test termination. There were no differences in heart-rate profile during exercise between healthy individuals and patients in indeterminate form, whereas patients with RBBB had more prevalence of chronotropic incompetence, lower exercise capacity and lower HRR compared with patients in indeterminate form and controls. A delayed decrease in the HR after exercise was found in 17 patients (15%), 9% in indeterminate form and 24% with RBBB, associated with older age, worse functional capacity, impaired chronotropic response, and ventricular arrhythmias during both exercise and recovery. By multivariable analysis, the independent predictors of a delayed decrease in the HRR were age (odds ratio [OR] 1.11; 95% confidence interval [CI] 1.03 to 1.21; p = 0.010) and presence of RBBB (OR 3.97; 95% CI 1.05 to 15.01; p = 0.042). A small proportion (15%) of asymptomatic Chagas patients had attenuated HRR after exercise, being more prevalent in patients with RBBB compared with patients in indeterminate form and controls.